An in-vitro study on the alterations induced by Mycoplasma arginini on cell cultures and virus titres - INDRANI, B K; UPADHYE, A S; BHANUPRAKASH, V (The Indian Journal of Animal Sciences, 2013)
After 4 days of post-infection (dpi) of Madin Darby bovine kidney (MDBK) cell monolayers with Mycoplasma arginini, rounding of cells, vacuolation in the cytoplasm and lysis of cells in the monolayer thereby creating empty space, lysis and condensation of karyon along with perinuclear hallowing were observed. In VERO cell monolayers. Mycoplasma arginini, induced enlargement, granulation and vacuolation in the cytoplasm, empty spaces in the mono layers and presence of clumped masses in the karyon. At a dilution of 10.7, and above and IO.K and above of Mycoplasma arginini produced no observable alterations in MDBK and VERO cell monolayers respectively. Mycoplasma arginini decreased the titre of infectious bovine rhinotracheitis virus (IBRV) 10 fold when it was cultivated in MDBK cell line.